Labor market policies during an epidemic - Serdar Birinci; Fatih Karahan; Yusuf Mercan; Kurt See (Federal Reserve Bank of New York, 2020)
We study the positive and normative implications of labor market policies that counteract the economic fallout from containment measures during an epidemic. We incorporate a standard epidemiological model into an equilibrium search model of the labor market to compare unemployment insurance (UI) expansions and payroll subsidies. In isolation, payroll subsidies that preserve match capital and enable a swift economic recovery are preferred over a cost-equivalent UI expansion. When considered jointly, however, a cost-equivalent optimal mix allocates 20 percent of the budget to payroll subsidies and 80 percent to UI. The two policies are complementary, catering to different rungs of the productivity ladder. The small share of payroll subsidies is sufficient to preserve high-productivity jobs, but it leaves room for social assistance to workers who face inevitable job loss.
Keywords: E24; E62; J64; 330; COVID-19; fiscal policy; labor productivity; unemployment; job search